1980
DOI: 10.1111/j.1399-0004.1980.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wolf‐Hirschhorn syndrome

Abstract: Four new cases of the Wolf-Hirschhorn syndrome are presented, two of which were due to t(4;22)mat. Review of the literature (more than 100 cases of the Wolf-Hirschhorn syndrome) showed that 13 % of all the reported cases were not mutations but segregations of parental chromosomal aberrations, primarily translocations. Similar data were obtained previously for other deletions (5p--, 18p--, 1Sq-). Analysis of data on some "new" deletion syndromes (4q--, 8p-, 9p-, lop-, l l p -, llq-) revealed that 14.5% were inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(39 citation statements)
references
References 31 publications
0
37
0
2
Order By: Relevance
“…The largest study (based on 108 cases) on the rate of unbalanced translocations in WHS indicated that approximately 13% of WHS cases had a derivative 4 due to a parental translocation and approximately 1.6% of cases had a de novo unbalanced translocation, making the total approximately 15%. 2 Other smaller studies (based on 22 -25 cases) have indicated that the rate of unbalanced …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest study (based on 108 cases) on the rate of unbalanced translocations in WHS indicated that approximately 13% of WHS cases had a derivative 4 due to a parental translocation and approximately 1.6% of cases had a de novo unbalanced translocation, making the total approximately 15%. 2 Other smaller studies (based on 22 -25 cases) have indicated that the rate of unbalanced …”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms leading to the deletion of 4p16.3 include cytogenetically visible de novo 4p terminal and interstitial deletions (50 -60%), de novo microdeletions detected by fluorescence in situ hybridization (FISH) using a probe for the critical region (25 -30%), or an unbalanced translocation either de novo or inherited from a familial balanced translocation (approximately 15%). 1,2 A portion of the clinical variation appears to be due to differences in the size of the deletion on 4p. 3 -5 However, many patients do not fit into a strict correlation between size of the deletion and severity of the syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…It had been proven that the larger deletion, the more severe congenital deformities one presents [1,12,17]. The other congenital defects include muscle hypotonia and urinary tract malformations (such as renal agenesis, oligomeganephronia, bladder exstrophy, cystic dysplasia/hypoplasia and obstructive uropathy) [18].…”
Section: Congenital Defectsmentioning
confidence: 99%
“…4 Previously, approximately 75% of cases were considered to be due to de novo terminal deletions, 5,6 13% from unbalanced translocations and the remainder from a more unusual cytogenetic abnormality. More recent studies have suggested the relative frequencies of deletions, unbalanced translocations and other causes to be 55%, 40% and 5%, respectively.…”
Section: Wolf-hirschhorn Syndrome (Whs; Omim 194190) Is a Contiguous mentioning
confidence: 99%